PROGRAM PENELAAHAN ALKITAB BAGI PEMUDA DI JEMAAT GMIT KAISAREA BTN-KOLHUA: SEBUAH PERSPEKTIF PEMBANGUNAN JEMAAT - William Cornelis Mbuilima; Mefibosed Radjah Pono (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2026)
This study examines the role of Bible Exploration (BE) as a sermon preparation medium programmed by the Youth Service Support Unit (UPP) of GMIT Kaisarea BTN-Kolhua, from the perspective of church development. BE is considered strategic in enhancing the quality of relevant and transformative sermons. Using a qualitative phenomenological approach, this research explores participants' experiences through observations, interviews, and literature reviews. The findings indicate that BE in Kaisarea often experiences functional distortion, where participants tend to be passive and overly reliant on BE leaders. This hampers theological capacity development and youth participation in ministry. As a solution, BE needs revitalization to foster independent reflection and deeper theological exploration. This study highlights the significance of BE as a theological formation tool that supports faith growth and sustainable church development.